Carpal tunnel syndrome caused by supernumerous lumbrical muscle in hemihyperplasia of the upper extremity = Syndrome du canal carpien causé par un muscle lombrical surnuméraire chez un patient atteint d’hémihyperplasie - Leclère, Franck Marie Patrick; Unglaub, Frank; Gohritz, Andreas; Hahn, Peter (Neurochirurgie, 2012)
Hemihyperplasia of the upper extremity is a rare pathology that occurs in 1/86,000 births. Carpal tunnel syndrome may be associated with this disease.…
Gesehen am 17.04.2018